Relative motion wave functions and spectroscopic factors in 5Hedt+d channel - Afanasyeva, N.V.; Burkova, N.A.; Zhaksybekova, K.A.; Kosanov, I.A. (Recent Contributions to Physics, 2013)
Within the two-body at-model for 7Li nucleus the relative motion wave functions in 5He+d channel have been built by using the projecting method in the dynamic potential cluster model. It is necessary to note, that in this calculations the {dt} configuration of 5He nucleus has been taken into account. The graphs of obtained 5He+d relative motion wave functions at the various values of the oscillatory parameter of α-particle are presented. S-wave of the relative d5He motion wave function, obtained in this work within the {dt} configuration of 5He nucleus, doesn't have a node in contrast to the corresponding one obtained earlier within the {an} configuration of 5He nucleus. Obtained functions have been used for calculation of the spectroscopic Sd-factors of the deuteron separation from nucleus. Also the comparative analysis of the obtained spectroscopic Sd -factors with corresponding ones calculated earlier within the {an} configuration of this nucleus has been performed.